2008
DOI: 10.1161/strokeaha.107.513234
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Events in Transient Ischemic Attack and Minor Stroke

Abstract: FRCPC; for the VISION study groupBackground and Purpose-The risk of a recurrent stroke after transient ischemic attack (TIA) or minor stroke is high.Clinical trials are needed to assess acute treatment options in these patients. We sought to evaluate the type of recurrent events and to identify which subsets of patients are at risk for recurrent events. Methods-One hundred and eighty patients with TIA or minor stroke were examined within 12 hours and underwent brain MRI within 24 hours. Any neurological deteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 33 publications
1
86
0
5
Order By: Relevance
“…Among those with a neurologic deficit lasting longer than 24 hours, the risk of subsequent stroke varies, with particularly high risk, comparable to that of time-defined TIA, observed in those with nondisabling symptoms and lower risk in those with major or disabling deficits. 39,40 It has been proposed that a new syndrome-transient symptoms with infarction-should be recognized because of the differing prognosis between those with transient symptoms with and without infarction and those with a permanent deficit. 15 In conclusion, we have found that subcategorization of patients with TIA as defined by time-based criteria into tissue-positive and tissue-negative groups yields helpful prognostic information, especially when brain infarction is found on DWI.…”
Section: Figure Pooled Analysis Of Association Between Abcd2 Score Anmentioning
confidence: 99%
“…Among those with a neurologic deficit lasting longer than 24 hours, the risk of subsequent stroke varies, with particularly high risk, comparable to that of time-defined TIA, observed in those with nondisabling symptoms and lower risk in those with major or disabling deficits. 39,40 It has been proposed that a new syndrome-transient symptoms with infarction-should be recognized because of the differing prognosis between those with transient symptoms with and without infarction and those with a permanent deficit. 15 In conclusion, we have found that subcategorization of patients with TIA as defined by time-based criteria into tissue-positive and tissue-negative groups yields helpful prognostic information, especially when brain infarction is found on DWI.…”
Section: Figure Pooled Analysis Of Association Between Abcd2 Score Anmentioning
confidence: 99%
“…Recent magnetic resonance imagaing studies suggest that early strokes are in fact a progression of the initial event, and it may be the case that a subset of our patients with early stroke represented either fluctuating lacunar syndromes, or infarction following partial large vessel occlusions. 16 Additional studies with baseline computed tommography-angiography and/or magnetic resonance imaging are required to explore this.…”
Section: Research Implicationsmentioning
confidence: 99%
“…Additionally, Arnold et al have shown that a normal angiogram portends a good prognosis [10]. Cerebral transient ischemic attacks in patients with large vessel occlusion have been found to have a 40% higher rate of second stroke than those with a normal MRA [11].…”
Section: Discussionmentioning
confidence: 99%